GWAS for behavioral traits in golden retrievers identifies genes implicated in human temperament, mental health, and cognition - Enoch Alex; Paul Gennotte; Anna Morros Nuevo; Yunzhu Yu; Benjamin Keep; Megan Sullivan; Daniel Mills; Varun Warrier; Eleanor Raffan (Proceedings of the National Academy of Sciences, 2025)
Dogs display temperamental and behavioral variation between individuals, just as psychiatric, temperamental, and cognitive traits vary in humans. In both species, these traits are highly heritable, yet causal genes remain incompletely understood. We performed 14 genome-wide association studies (GWAS) for behavioral traits quantified using the Canine Behavioral Assessment and Research Questionnaire (C-BARQ) in ~1,000 golden retrievers, identifying 12 genome-wide significant loci ( P < 2.97 × 10 −6 ) for 8 traits and 9 additional loci exceeding a suggestive threshold ( P < 1 × 10 −5 ). A human phenome-wide association study (PheWAS) showed that most of the 18 canine positional candidate genes identified were associated with one or more of 190 psychiatric, temperamental, or cognitive traits in humans (7/12 genes at genome-wide loci and 5/9 at suggestive loci). For example, a genome-wide significant locus near PTPN1 (dog-directed aggression) overlapped with human measures of Intelligence, Educational attainment, and major depressive disorder. The gene ROMO1 was within a genome-wide significant locus for trainability in dogs and associated with intelligence, depression, irritability, and sensitivity/hurt feelings in humans. Other genes located at genome-wide significant loci associated with behavioral, psychiatric, temperamental, or cognitive traits in both species included PRDX1(dog-directed fear), VWA8 (touch sensitivity) , ITPR2, and ADGRL2/LPHN2 (trainability), and ADD2 (stranger-directed fear). From suggestive loci we also found cross-species associations for HUNK, and ZC3H12C, (dog-directed fear), SLC35F6 and IGSF11 (separation-related problems). These results suggest that shared genetic and molecular mechanisms underlie complex behavioral and temperamental states across species and may inform our understanding of emotional states driving undesirable behaviors in dogs.